Olga Ginesi (1894-1943): recovery of a voice - Riquelme Ríos, Judith (Cuadernos Judaicos, 2021)
The article describes and analyzes specific aspects of Olga Ginesi's personal and professional life in the context of fascist Italy and the Second World War. The objective of understanding the past and present of this approach and making known her legacy as a creative author of children's books.The article is organized into four sections. First, the writers' environment and the cultural patterns that emerged in the period studied are briefly analyzed.Second, Ginesi's biography is studied.Third, reference is made to the bibliographic production that arises in his career.And finally, the first steps of the implications of its premature disappearance are examined.